Structural Characterization of Sulfated Polysaccharide Isolated From Red Algae (Gelidium crinale) and Antioxidant and Anti-Inflammatory Effects in Macrophage Cells - Pei, Yu; Yang, Shengtao; Xiao, Zhenbang; Zhou, Chunxia; Hong, Pengzhi; Qian, Zhong-Ji (Frontiers in Bioengineering and Biotechnology, 2021)
Gelidium crinale, the red algae belonging to Geliaceae Gelidium, is a traditional edible and industrial alga in China. A sulfated polysaccharide (GNP) is successfully separated from Gelidium crinale by acid extraction and two-step column chromatography. Chemical analysis showed that the molecular weight of GNP was 25.8 kDa and the monosaccharide composition had the highest galactose content and confirmed the presence and content (16.5%) of sulfate by Fourier transform infrared spectroscopy (FT-IR) spectrometry as well as barium chloride-gelatin methods. In addition, the effect of GNP on lipopolysaccharide (LPS)-induced oxidative stress and inflammation in macrophages was also evaluated. The research results showed that GNP had fairly strong scavenging activities on 2,2′-azino-bis(3-ethylbenzothiazoline-6-sulfonic acid) (ABTS) radical, hydroxyl radical, and 1,1-diphenyl-2-picrylhydrazyl (DPPH) radical and had Fe2+-chelating ability in a dose-dependent manner. At the same time, it significantly inhibits the expression of inducible nitric oxide synthase (iNOS) and cyclooxygenase-2 (COX-2) and the production of pro-inflammatory cytokines in RAW 264.7 cells induced by LPS through blocking the mitogen-activated protein kinase (MAPK)/nuclear factor kappa beta (NF-κB) signaling pathway. These results indicate that GNP may be a latent component anti-inflammation in pharmaceutical and functional food industries.